Trust works! four keys to building lasting relationships - Blanchard, Kenneth H. (New York William Morrow, 2013)
Offers advice for building and maintaining trust in order to improve interpersonal harmony and cooperation, and thus create a more productive and healthy work environment or social group.
Keywords: Trust